The Effect of Abusive Supervision on Turnover Intention with Employee Engagement as Mediation - Firdaus, Anita; Tjahjono, Heru Kurnianto (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
Supportive leadership enhances organizational performance, whereas abusive supervision undermines employee engagement and increases turnover intention. This study advances leadership and human resource research by applying Conservation of Resources (COR) Theory to clarify how employee engagement operates as both a psychological resource and a mediating mechanism under abusive supervisory conditions. Using a quantitative approach, data were collected from 195 nursing staff at Stella Maris Hospital Makassar through purposive sampling and analyzed using Structural Equation Modeling (SEM) with AMOS 24. The results show that abusive supervision significantly elevates turnover intention while reducing employee engagement. Employee engagement directly lowers turnover intention and partially mediates the relationship between abusive supervision and employees’ intention to leave. These findings extend COR Theory by empirically demonstrating the resource-depleting role of destructive leadership in healthcare settings. Practically, the study highlights the importance of minimizing abusive supervisory behaviors and strengthening supportive leadership to preserve engagement and reduce nurse turnover.